Food Choices and Hypertension Among Rural Thais: Evidence From a Discrete Choice Experiment - Pimbucha Rusmevichientong; Helen Nguyen; Celina Morales; Jessica Jaynes; Michele M. Wood (Frontiers Media S.A., 2022)
Objective: The rural northern region of Thailand exhibits the highest rate of hypertension. This study explored hypertensive-related food choices between normotensive and hypertensive people residing in rural northern Thailand to determine which food attributes influence their choices.Methods: The study conducted a discrete choice experiment (DCE) survey among Thai adults residing in rural northern Thailand (n = 403) to estimate the relative importance of four food attributes, including food preparation, price, taste, and amount of salt. A mixed logit model was used to analyze the data from the DCE.Results: The first and second most important attributes in both hypertensive and normotensive groups were the amount of salt and food preparation at home, respectively, followed by price and taste. Specifically, the normotensive group was more attentive to the amount of salt in their food than their hypertensive counterparts.Conclusion: Intervention programs in rural communities may benefit from focusing their attention on embracing low-salt cultural foods and providing guidance on how to add flavor without additional salt or reduce high sodium seasonings without losing flavor when cooking.